2010
DOI: 10.1007/s10750-010-0455-9
|View full text |Cite
|
Sign up to set email alerts
|

Over-winter decomposition and associated macroinvertebrate communities of three deciduous leaf species in forest streams on the Canadian Boreal Shield

Abstract: Litter inputs to headwater streams were measured to characterize and describe input patterns to the streams and to quantify the relationships between leaf litter inputs and surrounding riparian characteristics in Boreal Shield forests. Our goal was to provide information on litter inputs to streams in the Boreal Shield to determine if partial-harvest logging of commercial trees within riparian reserves has the potential to cause significant changes to litter inputs. Total leaf litter comprised 87% deciduous le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
3
9
0
Order By: Relevance
“…One possible reason for this finding is that some regionally (across streams) varying (unmeasured) factor is correlated to the feeding circumstances, thus increasing the amount of variance explained by RSR in the analysis of each guild. For example, percentage of wetland in the catchment could indirectly influence the LSR of filterers (LeCraw & Mackereth 2010) or riparian tree species richness could influence the LSR of shredders (Muto, Kreutzweiser & Sibley 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for this finding is that some regionally (across streams) varying (unmeasured) factor is correlated to the feeding circumstances, thus increasing the amount of variance explained by RSR in the analysis of each guild. For example, percentage of wetland in the catchment could indirectly influence the LSR of filterers (LeCraw & Mackereth 2010) or riparian tree species richness could influence the LSR of shredders (Muto, Kreutzweiser & Sibley 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This also suggests that macroinvertebrates could be more sensitive to food resources than to temperature changes. Many boreal stream studies also demonstrated that macroinvertebrates activity still active under low temperatures and may play a larger role in litter decomposition ( Irons et al, 1994 ; Muto et al, 2011 ). After that, the macroinvertebrate density decreased during thawing period, due to decrease in litter nutrient content and increase in hydrological disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…in ON. However, many of the less abundant taxa did not show this pattern, which might lead to similar shredder taxonomic richness, and community evenness and structure between home‐derived and foreign litter overall within the same litter pair (see also Muto, Kreutzweiser, & Sibley, ). In this study, we did not compare λ F and shredder colonisation between cedar species.…”
Section: Discussionmentioning
confidence: 99%